Spontaneous heterotopic mesenteric ossification around the pancreas causing duodenal stenosis: A case report with literature review. (April 2021) - Choi, Hanlim; Choi, Jae-Woon; Ryu, Dong Hee; Woo, Chang Gok; Kim, Ki Bae
Highlights: Heterotopic mesenteric ossification (HMO) is a rare condition that can lead to small bowel obstruction, which may require corrective surgery. Spontaneously occurring HMO can be occurred, but it is very rare. The peripancreatic HMO with severe fibrosis can occur duodenal stenosis, and it is mimicking periampullary cancer. Large heterotopic ossifications can be diagnosed by radiologic examination, but in small cases it is difficult to diagnose except for histological examination after surgery. Abstract: Introduction and importance: Heterotopic mesenteric ossification (HMO) is a rare condition that can be hereditary or nonhereditary. It can lead to small bowel obstruction, which may require corrective surgery. Most affected patients have a history of abdominal surgery or trauma. Spontaneously occurring HMO is even rarer, with only 7 cases reported till date. There has been no previous report of spontaneous peripancreatic HMO. Case presentation: A 60-year-old man presented with complaints of recurrent nausea and vomiting for 2 months. Esophagogastroduodenoscopy revealed luminal stenosis and edematous changes involving the second and third parts of the duodenum but not its complete obstruction. Abdominopelvic computed tomography showed faintly enhanced thickening of the involved duodenal walls along with mild dilatation of the common bile duct. Considering the possibility of periampullary cancer, we performed a pylorus-preserving pancreaticoduodenectomy. Histopathological examination confirmed the diagnosis of HMO with extensive fibrosis involving the peripancreatic soft tissue. Clinical discussion: The peripancreatic HMO with severe fibrosis can occur duodenal stenosis, and it is mimicking periampullary cancer. However, the preoperative diagnosis of spontaneous HMO is difficult, and a diagnosis confirmed after surgery. Conclusion: Herein, we described our experience of managing a rare case of duodenal stenosis due to spontaneous HMO involving peripancreatic tissue.